Home in the woods - Wheeler, Eliza (Nancy Paulsen Books, 2019)
During the Great Depression six-year-old Marvel, her seven siblings, and their mother find a tar-paper shack in the woods and, over the course of a year, turn it into a home. Based on the author's grandmother's childhood; includes historical notes.